Effect of surface modification of silica nanoparticles by silane coupling agent on decontamination foam stability. (April 2018) - Sonn, Jong Suk; Lee, Ju Yeon; Jo, Seon Hui; Yoon, In-Ho; Jung, Chong-Hun; Lim, Jong Choo
Highlights: Surface modification of silica nanoparticles was characterized by active ratio. Effect of surface modified silica nanoparticles on foam stability was investigated. Foam stability was identified through optical and fluorescence microscope images. Abstract: The effect of surface modification of silica nanoparticles by Dimethyldichlorosilane (DMDCS) on decontamination foam stability was investigated by the measurement of decaying foam volume with time using a Foamscan. The hydrophobicity of silica nanoparticles modified by DMDCS was characterized by active ratio via a floating test and contact angle analysis. Contact angle measurement has shown that silica nanoparticles surface become more hydrophobic as DMDCS concentration increases. Foam stability test in unmodified silica particles-surfactant mixtures revealed that silica nanoparticles-surfactant stabilized foams are much more stable than surfactant-stabilized foams and certain level of surfactant concentration is required for the synergy between silica nanoparticle and surfactant. In foam stability test with modified silica particle-surfactant mixtures, it was found that silica nanoparticles with the proper level of hydrophobicity shows the best performance in foam stability and this result was supported by optical and fluorescence microscope images.